2019
DOI: 10.1007/s00167-019-05762-2
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative soft tissue laxity around knee was associated with less accurate alignment correction after hybrid closed-wedge high tibial osteotomy

Abstract: Purpose This study aimed to assess the effect of soft tissue correction due to knee joint laxity, which induces alignment error after hybrid closed‐wedge high tibial osteotomy (CWHTO). In addition, to verify whether postoperative soft tissue correction can be predicted from preoperative radiographic parameters. Methods A retrospective evaluation of data from patients treated by CWHTO in 2016–2019 was performed. Standing full‐length anteroposterior radiograph measurement was performed pre‐ and post‐surgery, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 25 publications
(41 reference statements)
0
27
0
Order By: Relevance
“…Finally, JLCA changes can be anticipated [4,19,45] as well as accounting for the changes in soft tissue correction [27,44]. An equation has been proposed to define the acceptable intra-articular correction with the aim of achieving a more anatomic osteotomy while considering JLCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, JLCA changes can be anticipated [4,19,45] as well as accounting for the changes in soft tissue correction [27,44]. An equation has been proposed to define the acceptable intra-articular correction with the aim of achieving a more anatomic osteotomy while considering JLCA.…”
Section: Discussionmentioning
confidence: 99%
“…The medial proximal tibial angle (MPTA) was defined as the medial angle between the tibial anatomic axis and the joint line of the proximal tibia. The joint line convergence angle (JLCA) was defined as the angle between the tangent to the subchondral plates of the femoral condyle and the tibial plateau authors recommend to perform stress radiographs [27,35,38,45,48] because varus/valgus laxity appears to be important to predict influence of soft tissue laxity on alignment correction [35,38]. Lee et al proposed the concept of latent medial laxity by subtracting the JLCA on the weight-bearing standing radiograph from the JLCA on the valgus stress radiograph stress, this is thought to represent the ability of the soft tissue to stretch from a standing position to the valgus stress position [27].…”
Section: Reviewmentioning
confidence: 99%
“…The weight-bearing line (WBL) was defined as a line drawn from the center of the femoral head to the center of the superior articular surface of the talus on long-standing radiographs. The WBL ratio was calculated as the percentage of the distance between the medial edge of the proximal tibia and the point where the WBL intersects the proximal tibia to the width of the tibial plateau (the medial plateau edge was considered 0% and the lateral edge was considered 100%) [ 7 ]. The mFTA was defined as the acute angle between the femoral mechanical axis drawn from the center of the femoral head to the center of the knee joint and the tibial mechanical axis drawn from the midpoint of the knee joint to the center of the superior articular surface of the talus [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…All statistical analyses were performed using SPSS 19.0 Software (IBM, Armonk, NY, USA), and a P value < 0.05 was considered statistically significant. The intraobserver and interobserver reliabilities of the radiological measurements were assessed by determining the intraclass correlation coefficient (ICC), which ranged from 0 to 1, with 1 indicating perfect reliability and 0 indicating unreliability [ 7 ]. In this study, the intraobserver agreements ranged from 0.90 to 0.95, and the interobserver agreements ranged from 0.88 to 0.93, indicating high reliability and excellent measurement reproducibility.…”
Section: Methodsmentioning
confidence: 99%
“…4 Many authors have questioned what are the missing factors that explain the high frequency of HTO correction errors postoperatively. [11][12][13][14][15] Attempts to improve the accuracy of HTO corrections with computerized navigation have produced mixed results and recommendations. Stanley et al 16 reported on 117 knees with varus angulation and medial arthrosis undergoing opening wedge HTO; 52 were corrected using computer navigation and 65 were corrected with conventional techniques and intraoperative fluoroscopy.…”
Section: Cincinnati Sportsmedicine Research and Education Foundationmentioning
confidence: 99%